Bacterial communities structure in constructed wetlands for municipal and industrial wastewater treatment in Tanzania - Gerubin Liberath Msaki; Sadikiel E. Kaale; Karoli Nicholas Njau; Thomas J. Lyimo (Water Practice and Technology, 2023)
Bacteria are the largest and most essential microorganisms in wastewater treatment systems. Despite the vital role bacteria play in enhancing wastewater treatment, its community structure and diversity remain poorly known. This study elucidated bacterial diversity and community structure in constructed wetlands (CWs) for municipal and industrial wastewater treatment using a culture-independent approach. Analysis of physicochemical parameters and Illumina high-throughput sequencing of V3 and V4 hypervariable regions of 16S rRNA gene bacterial community was performed. The results showed that the Proteobacteria were dominant (48.66%) phyla across all CWs. The Gammaproteobacteria class (27.67%), family Comamonadaceae (35.79) and Genus Flavobacterium (4.35%) were dominant across studied CWs. Bacterial abundance increased from the inlet to the outlet, with CWs having a higher abundance around the outlet, showing a good performance. The Shannon–Wiener index showed the highest species diversity (H = 1.45) in Banana Investment Limited CWs treating industrial wastewater. This study found significant bacterial diversity across studied CWs, with higher abundance and diversity at the outlet indicating better performance than those with low abundance and diversity at the outlet. We recommend a longitudinal investigation at each CWs section to confirm and establish the role of bacterial diversity on the performance pattern of CWs. HIGHLIGHTS Bacterial community structures across different points and types of constructed wetlands (CWs) were assessed.; Proteobacteria were dominant phyla recovered across different types and points of CWs.; Industrial wastewater CWs had wider bacterial community diversity than municipal wastewater CWs.; Surface flow CWs had the highest bacterial reads and bacterial assemblage.;